The Influence of Vitamin a on Molecular Bio-mineral Tissue Development in Pigs (P02-012-19). (13th June 2019) - Clark, Adam; Kyriazakis, Ilias; Giles, Tim; Foster, Neil; Lietz, Georg
Abstract: Objectives: The objectives of this study were to identify differentially expressed transcripts and gene pathways in the vertebral bone of pigs receiving very high doses of vitamin A supplementation. Prior studies have ascertained that excessive vitamin A intake exhibits compartment-specific effects in bone tissue; these include regulating mineralisation genes in cortical bone containing bone marrow. Due to vertebral bone containing bone marrow, the hypothesis was that vitamin A will upregulate genes and pathways within vertebral bone that will favour bone mineralisation. Methods: A total of 64 indoor UK pigs, fed standard commercial diets, were split into 8 groups ( n = 8 per group) and received daily dosing of retinyl propionate (RP) (0 up to 10, 000 µg RP/kg BW) for 17 weeks. Vertebral bone was sampled from the 13 th thoracic vertebrae and RNA was extracted. RNA from control pigs and pigs receiving 10, 000 µg RP/kg BW was labelled and hybridised on an Agilent 4 * 44k microarray. Genespring was used to identify differentially expressed transcripts, and Ingenuity Pathway Analysis (IPA) was applied to recognise gene pathways associated with vitamin A supplementation. qRT-PCR was then performed to confirm differential gene expression on selected biomarkers. Kruskal-Wallis test was used to determine significant changes in gene expression in response to vitamin A dose. Results: A total of 318 transcripts were observed to be differentially regulated > 2-fold in the vertebral bone of pigs receiving 10, 000 µg RP/kg BW, 199 transcripts (62.6%) were observed to be upregulated ( P < 0.05). Genes relating to Rho-GTPases and regulation of cytoskeletal dynamics, such as CDC42 and FLNA, persisted among canonical pathways ( P < 0.05). qRT-PCR confirmed an 8.17-fold upregulation of FLNA in vertebral bone of pigs receiving 3000 µg RP/kg BW ( P < 0.01), but no clear effect of treatment was observed on CDC42 expression ( P = 0.147). Conclusions: Due to its role in the regulation of cytoskeletal reorganisation, of which subsequently affects both bone formation and resorption, the results suggest that high vitamin A intake potentially influences bone metabolism through interacting with the Rho-GTPase pathway. Funding Sources: Bill and Melinda Gates Foundation.